Stabilization of nano-sized structures in the volume of single-crystalline silicon for photoconverters - Dovbnya, A.N.; Yefimov, V.P.; Abyzov, A.S.; Rybka, A.V.; Bereznyak, E.P.; Zakutin, V.V.; Reshetnyak, N.G.; Blinkin, A.A.; Romas’ko, V.P.; Gabelkov, S.V.; Tarasov, R.V. (Вопросы атомной науки и техники, 2009)
The paper considers the possibilities of stabilization of microstructures created in the latent tracks in single-crystalline silicon by multicharged ions from the nuclear fragments formed as a result of heavy element photofission in the process of hydrogenating. The presence of hydrogen in the amorphous silicon structures leads to the clustering of vacancies, intrinsic interstitial and impurity atoms. For quantum structures, passivated with hydrogen atoms, the annihilation process is slowed down. In the process of annealing the silicon structures the strong (Si − H)n-bonds prevent the defect annihilation and thus stimulate the processes of precipitation and clusterization. Hydrogen, filling the irradiation-broken bonds, neutralizes their electrical activity. Optimal conditions for stabilisation of such structures are determined: irradiation doses, methods of hydrogenation and dissociation of H2, annealing parameters.